Принципи сегментування ринку плодово – ягідної продукції Півдня України - Колокольчикова, Ірина Володимирівна; Колокольчикова, Ирина Владимировна; Kolokolchykova, Iryna (My University, 2019)
UK: У статті оцінено стан розвитку ринку плодово-ягідної продукції, виявлено тенденції змін. Визначено, що сегментування ринку – це дієвий інструмент ефективного позиціювання на всіх ринках, набір вагомих чинників, які характеризують та створюють передумови формування попиту й ринкової пропозиції. Розглянуто складові процесу сегментування, принципи поділу на сегменти та основні показники їх оцінювання. Відзначено, що обсяги виробництва та ефективність виробничо-збутової діяльності залежать від правильного сегментування за географічним та демографічним принципами. Ресурсний потенціал галузі півдня України є розвинутим та максимально розгалуженим. Підкреслено, що разом з демографічними чинниками в умовах ринкових перетворень та конкурентної боротьби товаровиробників, важливим сьогодні є саме вплив психографічного та поведінкового сегментів. Саме ці неекономічні чинники є тими мотиваційними механізмами здійснення перших та повторних покупок. RU: В статье оценено состояние развития рынка плодово-ягодной продукции, выявлены тенденции изменений. Определено, что сегментирование рынка – это действенный инструмент эффективного позиционирования на всех рынках, набор весомых факторов, которые характеризуют и создают предпосылки формирования спроса и рыночного предложения. Рассмотрены составляющие процесса сегментирования, принципы деления на сегменты и основные показатели их оценивания. Отмечено, что объемы производства и эффективность производственно-сбытовой деятельности зависят от правильного сегментирования по географическому и демографическому принципам. Ресурсный потенциал отрасли юга Украины является развитым и максимально раскрытым. Подчеркнуто, что наряду с демографическими факторами в условиях рыночных преобразований и конкурентной борьбы товаропроизводителей важным сегодня является именно влияние психографического и поведенческого сегментов. Именно эти неэкономические факторы являются теми мотивационными механизмами осуществления первых и повторных покупок. EN: Production of fruit and berry products is of strategic importance. This production is favorite for ordinary citizens and it is used by all groups’ of the population of different age. Therefore, the demand for fruits and berries is constant, but it must be stimulated. The main methods of research are monographic, which makes it possible to study the phenomenon in the chronological plane. Thanks to the graphical method, most of the indicators are presented systematized and processed in this form. Application of methods of the system analysis and complex approach the process of segmentation of the market of fruits and berries of the South of Ukraine for the basic principles, the provided their qualitative assessment is considered. The paper presents a vision of the state of development of the market of fruit and berry products. Over the decade the development of the industry took place from intensive the way to extensive development. Modern areas of perennial plantations are three times smaller than now, but the gross production of fruits and berries is higher than in previous decades. This trend is confirmed by the indicator of productivity of gardens-yield, it is slowly but growing. It is determined that market segmentation is an effective tool for effective positioning in all markets, a set of significant factors that characterize and create prerequisites for the formation of demand and supply. The components of the segmentation process, the principles of creating segments and evaluation indicators are considered. It is indicated that the volume of production and sales are influenced by geographical and demographic factors. Natural resources of the South of Ukraine are the most favorable for gardening. It is emphasized that along with demographic factors, in the conditions of market transformations and competition of producers, it is important today to allocate segments on psychographic and behavioral content. Paying more attention to the study of consumer behavior, searching for levers of influence on the consciousness of the buyer and the perception of products, you can achieve a significant increase in sales; you can also create new segments in old markets. It is these non-economic factors are the motivational mechanisms for the implementation of the first and repeat purchases. Increasing their importance in the future will strengthen and create new demand and will give the opportunity to expand the supply of producers.
Principles of fruit and berry market segmentation in the South of Ukraine
Keywords: ринок; плодово-ягідна продукція; сегментування ринку; принципи сегментування; попит; пропозиція; мотивація; рынок; плодово-ягодная продукция; сегментирование рынка; принципы сегментирования; спрос; предложение; мотивация; market; fruit and berry products; market segmentation; segmentation principles; demand; supply; motivation